2011
DOI: 10.1016/j.ijsolstr.2011.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations and modeling of volume change induced by void growth in polyamide 11

Abstract: International audiencePolymers are known to be sensitive to hydrostatic pressure. The influence of stress triaxiality ratio on cavitation and damage has been highlighted in numerous studies. This paper proposes experimental investigations allowing the control of both the stress triaxiality ratio and the void distribution via microscopic observations of microtome-cut surfaces from interrupted tests. With the help of a finite element code, the Gurson-Tvergaard-Needleman model was calibrated by using these multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 48 publications
3
53
0
Order By: Relevance
“…According to Bélec, the first yield stress corresponds to a plasticization of the crystals, and the second one to a breakage of crystals. Moreover, a whitening of the material appears was between the first and second yields, indicating a damage by cavitations (Figure ) . Points 1–5 in Figure correspond to the pictures of the samples in Figure .…”
Section: Resultsmentioning
confidence: 86%
“…According to Bélec, the first yield stress corresponds to a plasticization of the crystals, and the second one to a breakage of crystals. Moreover, a whitening of the material appears was between the first and second yields, indicating a damage by cavitations (Figure ) . Points 1–5 in Figure correspond to the pictures of the samples in Figure .…”
Section: Resultsmentioning
confidence: 86%
“…The next step consists of checking which mechanical parameter is consistent with void column orientation (figure 2b). Previous study [2] showed that the radial distribution of voids for NT4 specimen follows the shape of the largest principal stress plot, whereas the largest principal strain distribution is rather "flat" (homogeneous strain in the net section). An attempt was then made here to plot the angle corresponding to the eigenvector of the largest principal stress and superimpose it to the orientation of void columns ( figure 2b).…”
Section: Modelingmentioning
confidence: 87%
“…Modeling of notched specimens can be achieved either by using formulae (analytical) or with the help of finite element (FE) analysis [2]. Analytical modeling is available under isochoric and small strain hypotheses [2]. In this work, FE modeling was used to overcome these limitations.…”
Section: Modelingmentioning
confidence: 99%
“…A video controlled-system is generally used to measure the volume variation with seven spots painted on the tensile specimen [1,2]. It is also possible to use inverse technique by identifying the parameters of a damage model by comparing and correlating same measurements obtained from experiments and finite element simulations and also taking into account the initial stress triaxiality ratio state [3][4][5]. Nevertheless, if you want to obtain the damage evolution without numerical simulations and for dynamic loadings, all these methods are not adapted for this particular condition.…”
Section: Introductionmentioning
confidence: 99%